Analysis of mitochondrial organization and function in the Drosophila blastoderm embryo - Sayali Chowdhary (Nature Portfolio, 2017)
Abstract Mitochondria are inherited maternally as globular and immature organelles in metazoan embryos. We have used the Drosophila blastoderm embryo to characterize their morphology, distribution and functions in embryogenesis. We find that mitochondria are relatively small, dispersed and distinctly distributed along the apico-basal axis in proximity to microtubules by motor protein transport. Live imaging, photobleaching and photoactivation analyses of mitochondrially targeted GFP show that they are mobile in the apico-basal axis along microtubules and are immobile in the lateral plane thereby associating with one syncytial cell. Photoactivated mitochondria distribute equally to daughter cells across the division cycles. ATP depletion by pharmacological and genetic inhibition of the mitochondrial electron transport chain (ETC) activates AMPK and decreases syncytial metaphase furrow extension. In summary, we show that small and dispersed mitochondria of the Drosophila blastoderm embryo localize by microtubule transport and provide ATP locally for the fast syncytial division cycles. Our study opens the possibility of use of Drosophila embryogenesis as a model system to study the impact of maternal mutations in mitochondrial morphology and metabolism on embryo patterning and differentiation.